Pogovori s starši in učenci kot orodje za razvijanje samostojnosti učencev pri šolskem delu - Grafenauer Ekart, Živa (Sodobna pedagogika, 2025)
Collaboration between parents and teachers is crucial for promoting children’s development. However, contemporary research and practices emphasise the importance of actively involving pupils in this collaboration. Nevertheless, the role of pupils is often neglected, which limits the possibilities for their development. In Slovenia, discussions with parents and pupils as a specific form of cooperation have not yet been systematically established, so it is proposed that this form of cooperation be incorporated into the broader context of pedagogical practice and international comparisons. As a part of the research, a pedagogical experiment was conducted in two fourth-grade classes at a selected elementary school. Structured discussions with parents and students were introduced in the experimental group, while traditional parent-teacher conferences were held in the control group. The broader aim of the research was to adapt and implement a model of conversations with parents and pupils and to test the possibility of implementing this cooperation model in practice, while the narrower aim was to examine how such conversations contribute to the development of pupils’ independence in school work. Both quantitative and qualitative research methods were used in the analysis, and data collection techniques included questionnaires, interviews, and focus groups. The results show that, according to students, parents, and teachers, the active involvement of students in cooperation between teachers and parents contributes to greater student independence in school work and better educational outcomes.
Keywords: home-school collaboration; prevzemanje odgovornosti učencev; role of teachers; sodelovanje med šolo in domom; student involvement; student responsibility; vključevanje učencev; vloga učiteljev